The liberalisation of agricultural trade as part of the WTO vs the possibilities of development of the Polish foreign trade in agri-food products - Pawlak, Karolina (Publishing House of the Wrocław University of Economics, 2009)
Of the numerous factors determining the level and structure of the world agricultural trade it is the processes of liberalisation of foreign exchange that deserve special attention. So far the most important decision concerning the access to the market, domestic support and export subsidies were made during the Uruguay Round GATT/WTO. The Agreement on Agriculture, which was negotiated then, started the process of reforms in agricultural trade and national agrarian policies aiming at the liberalisation of turnover between the signatories of the Agreement. Its further course was to have been agreed on during further negotiations. However, the new mandate of agricultural negotiations was passed only in six years following the end of the Uruguay Round, at the Ministerial Conference in Doha in November 2001. The end of the agricultural negotiations, which had thus begun and passing detailed decisions and the final agreement were expected to take place at the Ministerial Conference in Hong Kong, which was planned for December 2005. Due to the divergent negotiation stands taken by the main “players” in the Round the plan has not been realised yet. The aim of the article is to define the possibilities of development of trade exchange in the Polish agri-food sector in the conditions of potential liberalisation of the world agricultural trade and absence of further action taken in this direction. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 353-361